"If they believe, then so shall I": Perceived beliefs of the in-group predict conspiracy theory belief. (August 2021) - Cookson, Darel; Jolley, Daniel; Dempsey, Robert C.; Povey, Rachel
Conspiracy beliefs are widespread and can have detrimental consequences. As perceived social norms can exert a powerful influence on individuals, we investigated the relationship between perceived conspiracy belief norms and personal endorsement, and whether others' conspiracy belief is overestimated. In Study 1, UK university students ( N = 111) completed measures of their personal conspiracy beliefs and estimations of others' beliefs (an in-group and an out-group they chose, and a prescribed in-group). Perceived in-groups' belief strongly predicted personal conspiracy belief; perceived out-group's belief did not. Studies 2 and 3 replicated these findings in a British community sample ( N = 177) and in a UK parent sample ( N = 197), focusing on antivaccine conspiracy theories. All studies demonstrated that people overestimate the conspiracy beliefs of others. This is the first demonstration of the association between perceived in-group conspiracy belief social norms and individuals' personal conspiracy beliefs. Interventions challenging misperceived norms could be effective in reducing conspiracy beliefs.